The Palgrave Handbook of International Political Theory
XV, 467 p. 3 illus., 1 illus. in color.
Keywords: As the world confronts new challenges like pandemics and climate change, academic political theory has struggled to keep pace with events. Increasingly, our thinking must become international in scope. Focusing on themes from realism, sovereignty, and the nation-state to post-colonialism, gender, and indigeneity, these volumes attempt to bring political theory into the twenty-first century. — Steven B. Smith, Alfred Cowles Professor of Political Science, Yale University, USA This is a major new work by internationally renowned editors and cutting-edge contributors. The handbook pulls off the difficult feat of simultaneously canonizing and de-parochializing International Political Theory, by extending its historical genealogy as well as its regional and thematic reach. The results are presented in accessible chapters for the student of the new field. — Peter Niesen, Professor of Political Theory, University of Hamburg, Germany An excellent example of the handbook genre, focussing on a seminal yet often under-appreciated field: international political theory… This is a must-have collection for those passionate about political philosophy at the global level. — Brian Orend, Professor of Philosophy, University of Waterloo, Canada, and author of The Morality of War As a whole, the volume takes a global perspective, de-centring Europe by providing alternative voices and by contextualizing Europe within the broader narratives… It is just what one hopes for from a handbook. — Morag Goodwin, Professor of Global Law and Development, Tilburg University, Germany This handbook provides a comprehensive exploration of International Political Theory, which in its broadest terms examines the ways in which ideas about justice, sovereignty, and legitimacy shape international politics. The two volumes of the handbook cover topics ranging from the foundations of international political thought to the latest debates in the field. Chapters 4 and 13 are available through open access under a Creative Commons Attribution 4.0 International License via link.springer.com Howard Williams is Distinguished Honorary Professor, Cardiff University, UK. David Boucher is Professor of Political Philosophy and International Relations, Cardiff University, UK; Distinguished Visiting Professor, University of Johannesburg (2015– 25), South Africa. Peter Sutch is Professor of Political and International Theory, Cardiff University, UK; Visiting Professor, University of the Witwatersrand, South Africa. David Reidy is Professor of Philosophy, University of Tennessee, USA. Alexandros Koutsoukis is Lecturer in International Relations, University of Central Lancashire, UK.